A Digital Creative Industry, Webtoons: With a Focus on the Thai Webtoon Market - Kim, Sueun; Park, Kyungeun; Kim, Bongchul; Joo, Hyeonwook; Hyun, Yangwon (Journal of Urban Culture Research, 2025)
This study aims to explore the current state and challenges of the webtoon industry as a unique creative industry, focusing on the case of Thailand. First, it examines the characteristics and trends of the Webtoon market in Thailand, and how it contributes to the cultivation of a new creative industry. The study’s findings show that there is a dynamic relationship between the entry of major Korean webtoon platforms and the Thai publishing companies aided by an influx of Chinese capital that entered the market and established themselves as latecomers. In addition, the Thai-drama adaptations of Korean webtoons in Thailand have led to the transmedia adaptation of webtoons in the Thai market, thereby highlighting the potential of Thailand-based transnationalization of webtoons. This study illuminates how Thai webtoons function as a symbol of transnational cultural movement and elucidates their contribution to the creation of a new creative industry.